Drivers and triggers of international food price spikes and volatility - Tadesse, Getaw; Algieri, Bernardina; Kalkuhl, Matthias; von Braun, Joachim (Elsevier, 2014)
The objective of this study is to explore empirical evidence on the quantitative importance of supply, demand, and market shocks for price changes in international food commodity markets. To this end, it distinguishes between root, conditional, and internal drivers of price changes using three empirical models: (1) a price spike model where monthly food price returns (spikes) are estimated against oil prices, supply and demand shocks, and excessive speculative activity; (2) a volatility model where annualized monthly variability of food prices is estimated against the same set of variables plus a financial crises index; and (3) a trigger model that estimates extreme values of price spikes and volatility using quantile regressions. The results point to the increasing linkages among food, energy, and financial markets, which explain much of the observed food price spikes and volatility. While financial speculation amplifies short-term price spikes, oil price volatility intensifies medium-term price volatility.